International relations theory : a primer - Matthews, Elizabeth G. (Oxford University Press, 2017)
Ideal as a brief main text for IR Theories courses or as a supplemental text for IR, American Foreign Policy, or Global Studies courses, International Relations Theory: A Primer covers the main definitions, concepts, arguments, and criticisms regarding the five predominant IR theories and approaches used in the field today: realism, liberalism, constructivism, economic structuralism, and feminism. Bridging the gap between theory and practice, it helps students understand and critique the theories and apply them to real-world issues.